2004
DOI: 10.1016/j.clpt.2004.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of cyclosporine in kidney and heart transplant recipients and the influence of ethnicity and genetic polymorphisms in the and genes

Abstract: Patients carrying a CYP3A4*1B variant allele have a significantly higher oral cyclosporine clearance compared with patients homozygous for CYP3A4*1 . However, this genetic effect on cyclosporine disposition was small, and genotyping of transplant recipients for CYP3A4 is thus unlikely to assist in planning initial cyclosporine dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 45 publications
16
100
2
Order By: Relevance
“…In the present study, CYP3A4*1B decreased the inducible thiotepa clearance. Other authors have shown that CYP3A4*1B caused a modest decrease in systemic midazolam [38] and ciclosporin clearance [39,40], whereas others did not find an effect [41,42].…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, CYP3A4*1B decreased the inducible thiotepa clearance. Other authors have shown that CYP3A4*1B caused a modest decrease in systemic midazolam [38] and ciclosporin clearance [39,40], whereas others did not find an effect [41,42].…”
Section: Discussionmentioning
confidence: 96%
“…241); the impact of single nucleotide polymorphisms in ABCB1 is less clear. The largest cohort studies did not demonstrate an association of ABCB1 polymorphisms with cyclosporine pharmacokinetics (238,(242)(243)(244), and the effects of ABCB1 polymorphisms on tacrolimus pharmacokinetics are not consistent (238 -240,245,246). This demonstrates that ABCB1 variants, at maximum, explain tacrolimus pharmacokinetics to a limited degree.…”
Section: Systemic Levels Of Cyclosporine and Tacrolimusmentioning
confidence: 99%
“…21,42,[42][43][44][45][46][47][48][49][50][51] A further study has shown that the pharmacodynamic effects of cyclosporine on peripheral blood mononuclear cells were affected by the level of PGP expression, but not by the ABCB1 3435C4T genotype. 52 There was also no correlation between the 3435C4T genotype and PGP expression at the protein level in this study.…”
Section: Immunosuppressive Drugsmentioning
confidence: 99%